UEFA Champions League entry has not satisfied strategyproofness in three seasons - Csato, L. (Journal of Sports Economics, 2019)
This article investigates the qualification for the Union of European Football Association (UEFA) Champions League (CL), the most prestigious club competition in European football, with respect to the theoretical property of strategyproofness. We find that in three seasons (2015-2016, 2016-2017, and 2017-2018), the UEFA Europa League titleholder might have been better off by losing its match against the CL titleholder in their domestic championship. A straightforward solution is suggested in order to avoid the occurrence of this paradox. The use of an incentive compatible rule would have a real effect on the qualification in these three seasons of the UEFA CL.